Tinjauan Advokasi Terhadap Korban Trafficking Secara Yuridis - romlan prasodjo (Fakultas Hukum Universitas Darul Ulum, 2012)
In this study the formulation of the problem is how to determine the form of the HumanTrafficking? and what efforts are made to combat the trafficking ?. This study was conducted todetermine how trafficking can occur, as well as children and women trafficking network that has beenaccommodated as well.This type of research is a kind of research Qualitative-Normative circuitry makes the library (libraryresearch) as a data field that is studying the literature textbooks, lecture notes, and articles as well asother information contained in electronic media such as television, radio and computer (Internet)associated with this research. This study uses materials Secondary data research, namely researchmaterial obtained from literature studies of Legal Materials Primary, Secondary Legal Materials. Analysisof the data in this study was obtained through the study and Case Approach.The results in this study was Trafficking in persons is a form of crime committed by organized ofcrime. Performance of Trafficking action so neatly that it is difficult to break the chain which iscontinuous with each other. Trafficking in action, women and children are more dominant becomevictims because they are more vulnerable and weak to be a victim. Therefore, to prevent and trying tobreak the chain of Trafficking conducted efforts against Trafficking with this form of determinationagainst Trafficking law, opposition to trafficking.